2011
DOI: 10.1177/0267659111409971
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to sevoflurane during cardiopulmonary bypass

Abstract: Volatile anaesthetic agents are widely used for maintenance of anaesthesia in all kinds of surgical procedures. Despite the implementation of measures such as adequate ventilation of the operating room and the use of efficient scavenging systems, concern remains about the risks for occupational exposure, especially in situations associated with an increased risk of anaesthetic gas waste, such as with the use of volatile anaesthetic agents on cardiopulmonary bypass. The present contribution reports the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Chronic occupational exposure to low concentrations of sevoflurane has been discussed to have adverse effects on the health of health care workers [ 3 ]. Even though evidence is not clear on that issue occupational exposure limits and other ceiling value recommendations were published by governmental and health care organizations [ 4 - 7 ]. To answer the question if MCC-IMS could be a fast and reliable alternative to other analytical methods we calibrated the device to sevoflurane concentrations of 10 – 250 ppbv.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chronic occupational exposure to low concentrations of sevoflurane has been discussed to have adverse effects on the health of health care workers [ 3 ]. Even though evidence is not clear on that issue occupational exposure limits and other ceiling value recommendations were published by governmental and health care organizations [ 4 - 7 ]. To answer the question if MCC-IMS could be a fast and reliable alternative to other analytical methods we calibrated the device to sevoflurane concentrations of 10 – 250 ppbv.…”
Section: Discussionmentioning
confidence: 99%
“…The calibration of the MCC-IMS showed very low LOD and LOQ. Previously, PIS, PTR-MS and PTR-ToF-MS were used for assessing sevoflurane room air concentrations [ 4 , 8 , 9 , 12 , 13 ]. In our study MCC-IMS showed detection limits lower than all these methods – even when compared to PTR-ToF-MS [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several factors are related to OR contamination by waste inhalational anesthetics (Box 1) 8 . The halogenated volatile anesthetics in OR atmosphere contribute to the pollution of the place and are related to occupational diseases, although investigations of its effects are not yet conclusive 9 . Chronic exposure has the potential to develop sensitivity to hepatitis, headaches, nausea, drowsiness, fatigue, and irritability 3 .…”
Section: Chemical Risksmentioning
confidence: 99%